ジシンハ ソクド イホウセイ カラ ミタ ナンキョク ショウワキチカ ノ チカク マントル ノ デカップリング - 久保, 篤規; クボ, アツキ; 金尾, 政紀; カナオ, マサキ; Kubo, Atsuki; Kanao, Masaki (1997)
P(論文) 昭和基地で広帯域地震計によって記録されたモホ面でのPs変換波に対してS波スプリティングの解析を行い, 地殻内の地震波速度の異方性の主軸方位, 遅延時間差を求めた。すでに報告されている, SKSスプリティングによるマントルの異方性の特徴と比較することにより, この地域が受けた変形との関係を議論した。地殻部分のS波スプリティングは平均的にN50°W方向に速く, 遅延時間差は0.5秒であり, 速度の速い方位はマントルの場合(N49°E)とほぼ直交する。地殻の異方性のみであれば部分的にはゴンドワナ大陸の分裂でも説明できるが, 観測された地殻-マントル間でデカップルした異方性が生じる原因としては, 5億年前の衝突型の変成作用に伴う変形が最も考えやすい。大陸地殻の衝突に特徴的な地殻とマントルの剥離が起こり, その後地殻は横方向にextrusionし, マントルが沈み込むという形態をとっていれば, 地震波速度異方性から予想されるそれぞれの流動方向を説明可能である。 We analyzed shear wave splittings in the crust beneath Syowa Station, using Moho converted Ps waves. Three set of receiver functions and stacked receiver functions from Tonga events are analyzed. Results are interpreted by conbining with seismic anisotropy in the mantle, which have been revealed by SKS splitting. The observed fast polarized direction of crustal shear wave splitting shows N50°W, which is nearly perpendicular to that in the mantle (N49°E). Delay times of crustal anisotropy reach 0.5s. Although part of crustal anisotropy can be caused by the deformation due to Gondwana's break up, the most plausible explanation of crust-mantle decoupled anisotropy is related to the collisional deformation 500 Ma. If delamination between the crust and the mantle occurred in a former stage of metamorphism with subsequent crustal extrusion and mantle subduction, then observed seismic anisotropy in both the crust and the mantle can be explained. departmental bulletin paper